1997
DOI: 10.1074/jbc.272.5.3109
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Intronic Enhancer of the Human Ciliary Neurotrophic Factor Receptor (CNTFRä) Gene by the TR4 Orphan Receptor

Abstract: A conserved hormone response element, CNTFR-DR1 (5-AGGTCAGAGGTCAGG-3), has been identified in the 5th intron of the ␣ component of the ciliary neurotrophic factor receptor (CNTFR␣) gene for the human TR4 orphan receptor (TR4). Electrophoretic mobility shift assay showed a specific binding with high affinity (K d ‫؍‬ 0.066 nM) between TR4 and the CNTFR-DR1. A reporter gene assay using chloramphenicol acetyltransferase demonstrated that the 5th intron of CNTFR␣ has an enhancer activity which could be induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…Moreover, compared with the marginal suppression of TR2 on CpLuc reporter activity, TR4 has a much stronger suppressive effect on CpLuc reporter activity (data not shown), suggesting that TR4 may play a significant role in this regulation. Also, our data suggest that simple competition for binding to the DR1 site by these two nuclear receptors may not fully account for their distinct regulation of HBV core gene expression, because both nuclear receptors regulate target genes through binding to the DR sites (19,38). The detailed mechanisms underlying the distinct regulation of HBV gene expression by these two closely related orphan receptors remain unclear.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Moreover, compared with the marginal suppression of TR2 on CpLuc reporter activity, TR4 has a much stronger suppressive effect on CpLuc reporter activity (data not shown), suggesting that TR4 may play a significant role in this regulation. Also, our data suggest that simple competition for binding to the DR1 site by these two nuclear receptors may not fully account for their distinct regulation of HBV core gene expression, because both nuclear receptors regulate target genes through binding to the DR sites (19,38). The detailed mechanisms underlying the distinct regulation of HBV gene expression by these two closely related orphan receptors remain unclear.…”
Section: Discussionmentioning
confidence: 79%
“…Earlier studies indicated that TR2 and TR4 could modulate the expression of a set of genes through binding to the same HREs (19,38). Interestingly, Yu et al (14) reported that TR2 could only repress pre-C RNA, but not C RNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro data suggest that TR4 functions as a master regulator to modulate many signaling pathways, including induction of the ciliary neurotrophic factor alpha [5, 6], interfering with retinoic acid receptor/retinoid X receptor [7], thyroid receptor [8], androgen receptor [9], and estrogen receptor-mediated pathways [10], and facilitating viral infection and propagation of HPV-16 and SV40 [11]. Mice lacking Tr4 ( TR4KO ) have high rates of early postnatal mortality, show significant growth retardation [12], display reproductive defects in both genders [12, 13], abnormalities in spermatogenesis [14], reduced lipoprotein metabolism [15, 16], and reduced gluconeogenesis [17], as well as defects in cerebella development [18].…”
Section: Introductionmentioning
confidence: 99%